Evaluating the effectiveness of two video-based educational interventions to enhance knowledge about epilepsy in preschool children - Brabcová, Dana Buršíková; Kohout, Jiří; Mašková, Ivana; Lohrová, Kateřina (Epilepsy & behavior, 2025)
OBJECTIVES: Current research affirms that sufficiently high knowledge about epilepsy is crucial for reducing stigmatization and improving the quality of life for people with epilepsy. While educational interventions targeting older children, adolescents, and adults are relatively common, there is a notable lack of approaches suitable for preschool children. Building on our previous research, which focused on educational interventions using a game and a story, this study aims to evaluate the effectiveness of two video-based interventions, Campi the Seahorse and Adventure While Fishing, in children aged 5-6 years with no prior knowledge about epilepsy. METHODS: A total of 199 children participated in two intervention studies. Knowledge about epilepsy was assessed through interviews using an 11-item test that had been successfully employed in our previous intervention studies, demonstrating satisfactory internal consistency and construct validity. The level of knowledge was evaluated immediately after each intervention and one month later. Additionally, satisfaction with the intervention and its potential impact on epilepsy-related stigma were measured using a smiley-face scale. RESULTS: The Adventure While Fishing intervention demonstrated notable effectiveness compared to our previously developed intervention using an educational story. Its impact was also significant when compared to the level of knowledge observed in children aged 9-11 years with no prior exposure to epilepsy-related interventions. In contrast, the outcomes of the Campi the Seahorse intervention were significantly poorer across all comparisons, likely due to its insufficient coverage of key aspects of the topic. CONCLUSIONS: The results indicated that the Adventure While Fishing intervention was an effective approach to establishing basic knowledge about epilepsy within the targeted age group. In contrast, the Campi the Seahorse intervention would require further extension and/or modification to achieve sufficient effectiveness for this purpose.
Keywords: Epilepsy; epilepsie; audiovizuální záznam; Humans; Video Recording; Preschool; Educational video; dítě; Child; Female; zdraví - znalosti, postoje, praxe; Patient Education as Topic; lidé; předškolní dítě; ženské pohlaví; Male; Health Knowledge, Attitudes, Practice; vzdělávání pacientů jako téma; mužské pohlaví; Child, Preschool; Knowledge about epilepsy; Intervention